Prevalence of Pancytopenia/ Bicytopenia in Pediatric Population and its Association with Etiology Based on Bone Marrow Findings - Nida Khalid, Hajra Azhar, Javeria Afzal, Zeneara Saqib, Sundus Durrani, Muhammad Irfan (Pakistan Journal of Medical & Health Sciences, 2023)
Background: An important clinico-haematological condition known as pancytopenia or bicytopenia is brought on by a multitude of disease processes that either directly or indirectly affect the bone marrow. Aim: To ascertain the prevalence of cytopenias in the pediatric population presenting to a tertiary care hospital in Rawalpindi and its correlation with age and gender distribution, clinical presentation, and aetiology. Study Design: Descriptive cross-sectional study. Methodology: It was a descriptive cross-sectional study carried out at Holy Family Hospital in Rawalpindi’s hematology division. Using non-probability consecutive sampling, 253 individuals referred for bone marrow testing were included in the study, of which 108 patients had pancytopenia and 108 had bicytopenia. Data was gathered on the patient’s mode of presentation, clinical examination, full blood counts, and bone marrow analysis. The data were analyzed using SPSS 22, and descriptive statistics were computed. Using chi-square test with a P value of 0.05 was taken as significant. Results: Bicytopenia was discovered in (133)52.6% of patients and pancytopenia in (120)47.4% of patients. 139 (55%) of the 253 instances involved men, while 114 (45%) were women. Fever 225 (89%), bleeding symptoms 52 (20.5%), and bruising 36 (14.2%) were the most frequent presenting complaints. The most frequent result on examination was pallor234, which was followed by hepatomegaly118 (46.64%) and splenomegaly114 (45.05%). In the total blood count, bicytopenia (133), 52.6%, and pancytopenia (120), 47.4%, were the most common findings. Practical Implication: There is scarcity of such data on paediatric patients, and to the best of our knowledge, no study has analysed the paediatric bicytopenic / pancytopenic patient in our centre. Thus present study was planned inorder to determine the prevalence of different etiology of bicytopenia /pancytopenia and its association with clinico-haematological parameters. Conclusion: It was discovered that bicytopenia/pancytopenia was frequently the reason for bone marrow testing. Three common underlying etiologies acute leukaemia, megaloblastic anemia, and aplastic anemia were discovered. Keywords: Cytopenias, Bone Marrow, Pediatric Population, Clinico-haematological Parameters and Prevalence.